Effect of chaos noise on the learning ability of back propagation algorithm in feed forward neural network - Azian Azamimi; Uwate, Yoko; Nishio, Yoshifumi (Institute of Electrical and Elctronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/